0436 Sleep-RelatedPsychological and Behavioral Profiles inInsomnia With and Without Objective Short Sleep Duration. (27th April 2018) - Huang, Y; Lee, H; Yang, C
Abstract: Introduction: It has been proposed that there are two distinct insomnia phenotypes that could be differentiated by a cut-off of 6 hours in objectively measured (PSG or actigraph) sleep duration. The phenotype with short sleep duration, characterized by physiological hyperarousal, was found to be associated with activated HPA axis and higher cardiovascular and metabolic risks and comorbidity; the phenotype with longer sleep duration, characterized by cognitive-emotional and cortical arousal, was found to be associated with sleep misperception and a psychological profile with more emotional disturbances. A recent study further indicated that the first phenotype showed less response to cognitive behavioral therapy for insomnia. Since sleep-related psychological and behavioral factors are considered to be the main etiological factors for chronic insomnia, the present study aims to explore the profiles of these factors in the two phenotypes of insomnia Methods: 59 insomniacs (age=42.12 ± 12.14, 43 female) without comorbidity of psychiatric, medical or sleep disorders participated in this study. They went through one night of PSG and were required to complete a set of questionnaires including Dysfunctional Belief and Attitudes About Sleep (DBAS-30), Sleep Hygiene Practice Scale (SHPS), Pre-sleep Arousal Scale (PSAS), Insomnia Severity Index (ISI), Beck Anxiety index (BAI) and Beck Depression index (BDI). They were divided into two groups by a PSG TST cutoff of 6 hours, with 22 participants in short sleep duration group and 37 in longer sleep duration group. Results: One way ANOVAs were conducted to compare the psychological and behavioral variables between the two groups. No significant differences were found between the two groups in the total scores and subscale scores of the DBAS, SHPS, PSAS, ISI, BAI and BDI. Conclusion: Our results showed similar sleep-related psychological and behavioral profiles between insomnia patients with objective short and near-normal sleep duration. These results indicate that sleep-related psychological and behavioral factors may be developed along the chronicity of insomnia for both phenotypes. They should be the targets of treatment strategies for both types of insomnia. Support (If Any): Supported by the Ministry of Science and Technology, Taiwan (NSC104-2410-H-004-044-MY3).<!--EndFragment-->.